2023
DOI: 10.1111/echo.15625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hypertension on systolic and diastolic left ventricular function including segmental strain and strain rate

Abstract: Background Left ventricular (LV) systolic and diastolic functions are important cardiovascular risk predictors in patients with hypertension. However, data on segmental, layer‐specific strain, and diastolic strain rates in these patients are limited. The aim of this study was to investigate segmental two‐dimensional strain rate imaging (SRI)‐derived parameters to characterize LV systolic and diastolic function in hypertensive individuals compared with that in normotensive individuals. Methods The study sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…STE achieves this by acquiring images at a frame rate of 50-80 per second [57], allowing more accurate and comprehensive cardiac imaging. Further reinforcing the utility of STE, numerous studies have demonstrated that both LV and LA strain, along with strain rate, are reliable predictors of LV diastolic function [31,54,58,59]. These findings underscore the potential of STE as a transformative tool in the evaluation and management of cardiac function, particularly diastolic performance.…”
Section: Strain Imagingmentioning
confidence: 83%
See 1 more Smart Citation
“…STE achieves this by acquiring images at a frame rate of 50-80 per second [57], allowing more accurate and comprehensive cardiac imaging. Further reinforcing the utility of STE, numerous studies have demonstrated that both LV and LA strain, along with strain rate, are reliable predictors of LV diastolic function [31,54,58,59]. These findings underscore the potential of STE as a transformative tool in the evaluation and management of cardiac function, particularly diastolic performance.…”
Section: Strain Imagingmentioning
confidence: 83%
“…In a study involving normotensive controls and three groups of patients with different degrees of hypertension, segmental parameters exhibited apical-basal gradients, with the lowest values in the basal septal segments and the highest in apical segments. Only SRa remained consistent among segments but increased gradually with rising blood pressure [59]. SRE decreased, particularly longitudinally, without a significant rise in LV filling pressure, showing that strain is more sensitive than conventional methods in detecting reduced myocardial contractility in hypertensive patients before LV hypertension [108].…”
Section: Hypertensive Heart Diseasementioning
confidence: 90%
“…STE achieves this by acquiring images at a frame rate of 50-80 per second [59], allowing more accurate and comprehensive cardiac imaging. Further reinforcing the utility of STE, numerous studies have demonstrated that both LV and LA strain, along with strain rate, are reliable predictors of LV diastolic function [32,56,60,61]. These findings underscore the potential of STE as a transformative tool in the evaluation and management of cardiac function, particularly diastolic performance.…”
Section: Strain Imagingmentioning
confidence: 83%
“…In a study involving normotensive controls and three groups of patients with different degrees of hypertension, segmental parameters exhibited apical-basal gradients, with the lowest values in the basal septal segments and the highest in apical segments. Only SRa remained consistent among segments but increased gradually with rising blood pressure [61]. SRE decreased, particularly longitudinally, without a significant rise in LV filling pressure, showing that strain is more sensitive than conventional methods in detecting reduced myocardial contractility in hypertensive patients before LV hypertension [109].…”
Section: Hypertensive Heart Diseasementioning
confidence: 90%
“…Left ventricular (LV) global longitudinal strain (GLS) derived from two-dimensional speckle tracking echocardiography (STE) has been confirmed to accurately detect LV systolic dysfunction in various cardiovascular diseases, such as coronary artery disease [ 12 , 13 ], hypertension [ 14 ], and T2DM [ 15 ]. However, the association between the TyG index and LV GLS in obese patients is still unknown.…”
Section: Introductionmentioning
confidence: 99%